2010
DOI: 10.1159/000274463
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum γ-Glutamyltransferase and Chronic Kidney Disease among US Adults

Abstract: Background/Aim: Serum γ-glutamyltransferase (GGT), a biomarker of oxidative stress, is associated with an increased risk of diabetes and hypertension. However, it is not known whether higher serum GGT is independently associated with chronic kidney disease (CKD). Therefore, we examined the association between serum GGT levels and CKD in a representative sample of US adults. Methods: We conducted a cross-sectional study of 9,516 National Health and Nutrition Examination Survey 1999–2002 participants ≧18 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Some studies showed that serum GGT within the physiologic range independently predicted albuminuria among patients with or without hypertension or diabetes [11, 12], while another study showed that there was no association between increased levels of serum GGT and CKD [13]. The discrepancy among these studies was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that serum GGT within the physiologic range independently predicted albuminuria among patients with or without hypertension or diabetes [11, 12], while another study showed that there was no association between increased levels of serum GGT and CKD [13]. The discrepancy among these studies was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that serum GGT was correlated with SF, and they could synergistically affect the risk of type 2 diabetes [10]. Several but not all studies showed that GGT was associated with increased risk of CKD [1113]. Few studies analyzed the association between SF and CKD, especially the interaction between GGT and SF on CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Two cross-sectional studies using National Health and Nutrition Examination Survey data came to different conclusions. Whereas one study found a strong association between GGT and CKD [30], the other study found no such relation [31]. An investigation with a 3-year follow-up described an association between GGT and the development of CKD (defined as eGFR < 60 ml/min/1.73 m 2 ) in men without hypertension or diabetes [32].…”
Section: Discussionmentioning
confidence: 99%
“…These findings could explain the controversial report of Teppala et al (21) showing no significant association between elevated serum GGT and the prevalence of CKD defined as reduced eGFR of less than 60 mL/min/1.73 m 2 in the participants of the National Health and Nutrition Examination Study (NHANES) 1999-2002, versus that of Targher et al (20) showing a significant association with the prevalence of CKD defined as reduced eGFR and/or abnormal albuminuria in the same study program of NHANES 2001-2006, although both studies had a major limitation as cross-sectional observations.…”
Section: Discussionmentioning
confidence: 83%